Koordinasi Pemerintah Kabupaten Kampar Dalam Penanggulangan Bencana Kabut Asap - Rizka Khairunnisa; Roni Ekha Putera; Yoserizal Yoserizal (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Kampar Regency is one of the areas that are included in six areas prone to smog in Riau Province. Moreover, of the six smog-prone areas in Riau Province, Kampar Regency is also the district with the largest population of the other five regions. Thus, inevitably resulting in more and more people being affected by the emergence of smog. Thus, of course the Kampar Regency Government has coordinated with relevant agencies in overcoming this haze disaster. The purpose of this study was to determine and analyze the implementation of the coordination of the Kampar Regency Government in Haze Disaster Management. The research method used is qualitative descriptive through in-depth interviews with competent parties stating that in measuring coordination there are four main variables, namely unity of action, division of labor, communication and discipline. Based on the results of the study it can be concluded that the coordination of the Kampar Regency government in dealing the haze disaster has been running quite well.